Investigation of bend effect of tie bar on precast concrete slab construction - Raihana Farahiyah Abdul Rahman, 1993-, author; Izni Syahrizal Ibrahim, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Sarjana Kejuruteraan (Forensik)) - Universiti Teknologi Malaysia, 2018